2022
DOI: 10.1096/fj.202200784r
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory chemokine ( C‐C motif) ligand 8 inhibition ameliorates peritoneal fibrosis

Abstract: Peritoneal fibrosis (PF) is an irreversible complication of peritoneal dialysis (PD) that leads to loss of peritoneal membrane function. We investigated PD effluent and serum levels and the tissue expression of chemokine (C‐C motif) ligand 8 (CCL8) in patients with PD. Additionally, we investigated their association with PF in a mouse model. Eighty‐two end‐stage renal disease (ESRD) patients with PD were examined. CCL8 levels were measured via enzyme‐linked immunosorbent assays in PD effluents and serum and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In CHX-induced damage, Ccl8, the mouse functional analog of human CCL18 [40], was the most upregulated chemokine in the peritoneum, as we have observed in this study. Moreover, the functional blockade of CCL8, using a CCR8 inhibitor, prevented PM thickening and macrophage infiltration into the peritoneum [41,42]. In this study, we have found that JQ1 diminished the peritoneal Ccl8 overexpression.…”
Section: Discussionsupporting
confidence: 51%
“…In CHX-induced damage, Ccl8, the mouse functional analog of human CCL18 [40], was the most upregulated chemokine in the peritoneum, as we have observed in this study. Moreover, the functional blockade of CCL8, using a CCR8 inhibitor, prevented PM thickening and macrophage infiltration into the peritoneum [41,42]. In this study, we have found that JQ1 diminished the peritoneal Ccl8 overexpression.…”
Section: Discussionsupporting
confidence: 51%
“…Furthermore, the observed conducting channel migration and the resulting negative differential interlayer resistance occur without heterojunctions at room temperature. Our findings would pave the way for numerous electronic applications based on 2D vdW multilayers such as frequency multiplier, 40,41 random number generator, 42,43 multivalued logic circuits, 44,45 and neuromorphic computing. 46,47 To gain a better understanding of the carrier transport mechanism in 2D vdW multilayers, we briefly illustrate the direction of the vertical channel migration under electrostatic V G and V D bias conditions with VDC (Figure 5a,b).…”
Section: ■ Resultsmentioning
confidence: 81%
“…55 Studies showed that STAMBP can increase NACHT, LRR and PYD domains-containing protein 7 (NALP7) inflammasome and IL-1β levels to promote inflammation through deubiquitination. 56 60,61 We discovered that MCP2 can lower the likelihood of spondylolisthesis/spondylolysis, and more research is necessary to determine its involvement in spondylolysis and other nonunions. Among these 91 CIPs, TGF-β1 was not found.…”
Section: Associations Of Cips With Spondylolisthesis/ Spondylolysismentioning
confidence: 99%